(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study ascertained the perceptions of small and medium scale enterprises managers in Anambra State on the extent employees’ participation in decision making improved their work performance. Two research questions guided the study while four null hypotheses were tested at 0.05 level of significance. Descriptive survey research design was adopted for the study. The population of the study comprised 1124 managers of small and medium scale enterprises in Anambra State and a sample of 225 managers of small and medium scale enterprises in the Anambra State was selected through stratified simple random sampling technique. A 25-item validated questionnaire titled Questionnaire on Contributions of Employees’ Participation in Decision-Making and Organizational Performance (QCEPDMOP) was used for data collection. The questionnaire was structured on a 5-point likert scale. Test re-test was used for reliability. Pearson Product Moment Correlation was used to analyze the data to obtain reliability coefficient of 0.93 and 0.85 for clusters B1 and B2 respectively with overall reliability coefficient of 0.89. Out of the 225 copies of the questionnaire distributed, 209 were retrieved and used for data analysis. Mean, standard deviation, t-test and ANOVA were used for data analysis. Findings of the study revealed that employees’ participation in decision making improves their commitment and effective management of resources to a high extent. Also, that gender and years of experience did not affect employees’ participation in decision-making. Based on the findings, managers of SMEs in Anambra State should strive to bring in competent employees to the enterprise for effective management of the organization.